2014
DOI: 10.1371/journal.pone.0112213
|View full text |Cite
|
Sign up to set email alerts
|

Insight to the Epidemiology and Risk Factors of Extrapulmonary Tuberculosis in Tianjin, China during 2006-2011

Abstract: BackgroundThe proportion of extrapulmonary tuberculosis (EPTB) among all the reported tuberculosis (TB) cases has increased in different populations. Despite the large burden of TB in China, the epidemiology of EPTB in China remains largely understudied and the risk factors for having EPTB diagnosis in China have not been identified.MethodsTo gain insight to EPTB epidemiology in China, we analyzed TB surveillance data collected in Tianjin, China, during 2006 to 2011. The frequency of EPTB among all TB cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 20 publications
(21 reference statements)
6
49
1
Order By: Relevance
“…In Europe, same results were observed in Denmark [26] and in Croatia [7]. In the USA, unemployment was associated with EPTB [12,16]. This is the case too in China [27] and Japan too [28].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In Europe, same results were observed in Denmark [26] and in Croatia [7]. In the USA, unemployment was associated with EPTB [12,16]. This is the case too in China [27] and Japan too [28].…”
Section: Discussionsupporting
confidence: 67%
“…In another view, sometimes, treatment is proposed empirically based on clinical and radiological arguments. Studies conducted worldwide have identified several risk factors associated with the occurrence of EPTB: age [1,2,9], female sex [1,11,12], no vaccination [13], contact with TB patient [5,12,14], alcohol consumption [11,15], employment [13,16], diabetes [15] and HIV infection [1,11] particularly. Senegal, like many Sub-Saharan African countries, is facing the TB epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on the prevalence of ETB are quite contrasting and usually reflect local and regional differences, being difficult to reach any conclusions. [13][14][15][16][17][18][65][66][67][68] Even so, in some studies, lymphatic TB stands out as the most common form of ETB. [52][53][54] Some forms of TB were less frequent in our study than expected.…”
Section: -7mentioning
confidence: 99%
“…1,8,[11][12] The proportion of patients with extrapulmonary (ETB) or pulmonary TB (PTB) varies along different world regions. [13][14][15][16][17][18] ETB is more frequent in people with a compromised immune system, as is the case in HIV-infected patients. 11,12 Some patients have characteristics that put them at risk of acquiring TB.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in developed countries have revealed that, while the overall incidence of TB has been declining, the proportion of EPTB has increased [2,4]. Also Wang et al [8] in their comprehensive study from Tianjin, the fourth largest city in China with 13 million inhabitants, reported 10% EPTB between 2006 and 2011. Similar result, 13.3%, was noted in Taiwan by Lin and coworkers [9].…”
Section: Introductionmentioning
confidence: 99%